The dissipation of kinetic energy in the Lofoten Basin Eddy - Fer, Ilker; Bosse, Anthony; Ferron, Bruno; Bouruet-Aubertot, Pascale (Journal of Physical Oceanography, 2018)
Ocean microstructure, current, and hydrography observations from June 2016 are used to characterize the turbulence structure of the Lofoten Basin eddy (LBE), a long-lived anticyclone in the Norwegian Sea. The LBE had an azimuthal peak velocity of 0.8 m s−1 at 950-m depth and 22-km radial distance from its center and a core relative vorticity reaching −0.7f (f is the local Coriolis parameter). When contrasted to a reference station in a relatively quiescent part of the basin, the LBE was significantly turbulent between 750 and 2000 m, exceeding the dissipation rates ε in the reference station by up to two orders of magnitude. Dissipation rates were elevated particularly in the core and at the rim below the swirl velocity maximum, reaching 10−8 W kg−1. The sources of energy for the observed turbulence are the background shear (gradient Richardson number less than unity) and the subinertial energy trapped by the negative vorticity of the eddy. Idealized ray-tracing calculations show that the vertical and lateral changes in stratification, shear, and vorticity allow subinertial waves to be trapped within the LBE. Spectral analysis shows increased high-wavenumber clockwise-polarized shear variance in the core and rim regions, consistent with downward-propagating near-inertial waves (vertical wavelengths of order 100 m and energy levels 3 to 10 times the canonical open-ocean level). The energetic packets with a distinct downward energy propagation are typically accompanied with an increase in dissipation levels. Based on these summer observations, the time scale to drain the volume-integrated total energy of the LBE is 14 years. publishedVersion